2021
DOI: 10.1371/journal.pone.0247621
|View full text |Cite
|
Sign up to set email alerts
|

Berberine ameliorates vascular dysfunction by a global modulation of lncRNA and mRNA expression profiles in hypertensive mouse aortae

Abstract: Objective The current study investigated the mechanism underlying the therapeutic effects of berberine in the vasculature in hypertension. Methods Angiotensin II (Ang II)-loaded osmotic pumps were implanted in C57BL/6J mice with or without berberine administration. Mouse aortae were suspended in myograph for force measurement. Microarray technology were performed to analyze expression profiles of lncRNAs and mRNAs in the aortae. These dysregulated expressions were then validated by qRT-PCR. LncRNA-mRNA co-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Numerous studies have verified that vascular endothelial cell dysfunction and lncRNA activity may together be associated with hypertension ( Lorenzen and Thum, 2016 ; Konukoglu and Uzun, 2017 ). The levels of five lncRNAs were found to be modulated by the administration of 100 mg/kg berberine in mice with hypertention, which may preserve vascular endothelial cell function ( Tan et al, 2021 ). Endothelial microparticles (EMPs) are extracellular vesicles that are shed by the endothelium as a result of activation, injury, or apoptosis of endothelial cells, and are considered important biomarkers of the status of endothelial cells and vascular function ( Sun et al, 2016 ).…”
Section: Effects Of Berberine On Vascular Diseasesmentioning
confidence: 99%
“…Numerous studies have verified that vascular endothelial cell dysfunction and lncRNA activity may together be associated with hypertension ( Lorenzen and Thum, 2016 ; Konukoglu and Uzun, 2017 ). The levels of five lncRNAs were found to be modulated by the administration of 100 mg/kg berberine in mice with hypertention, which may preserve vascular endothelial cell function ( Tan et al, 2021 ). Endothelial microparticles (EMPs) are extracellular vesicles that are shed by the endothelium as a result of activation, injury, or apoptosis of endothelial cells, and are considered important biomarkers of the status of endothelial cells and vascular function ( Sun et al, 2016 ).…”
Section: Effects Of Berberine On Vascular Diseasesmentioning
confidence: 99%
“…Importantly, lncRNA ENSMUST00000155383, which was included in the 13 DE-lncRNAs we have identified, was coexpressed with Cacna1C, Itgav, Itga8, and Npnt. Also, our previous study revealed that lncRNA ENSMUST00000155383 mainly expressed in endothelial cells of the vasculature, which was downregulated in hypertensive mouse aortae (Tan et al, 2021). Altogether, we speculated the dysregulation of lncRNA ENSMUST00000155383 and the four related-mRNAs might play an important role in vascular endothelial dysfunction under hypertension.…”
Section: Discussionmentioning
confidence: 71%
“…Surprisingly, while transcriptomic profiles of AngII-treated organs/tissues are available in the kidneys ( 18 ), heart ( 19 ), or abdominal aortic aneurysm in ApoE-/- mice ( 20 ), the AngII treatment protocol varies widely between studies, and transcriptomic data on the arterial tissue of WT mice were rarely reported ( 21 23 ), with no attempt to analyze any legacy effect.…”
Section: Introductionmentioning
confidence: 99%